The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/ehjopen/oeab044
|View full text |Cite
|
Sign up to set email alerts
|

Is the contemporary care of the older persons with acute coronary syndrome evidence-based?

Abstract: Globally, ischaemic heart disease is the leading cause of death, with a higher mortality burden amongst older adults. Although advancing age is associated with a higher risk of adverse outcomes following acute coronary syndromes (ACS), older patients are less likely to receive evidence-based medications and coronary angiography. Guideline recommendations for managing ACS are often based on studies that exclude older patients, and more contemporary trials have been underpowered and produced inconsistent finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…To date, of the 5 randomized clinical trials specifically investigating an invasive strategy in older patients with NSTEMI, 4 have found no benefit of invasive treatment on the primary end point compared with conservative management, [130][131][132][133] whereas the other showed that an invasive strategy reduced recurrent MI and urgent repeat revascularization (Table 3). 134,135 The Italian Elderly ACS trial randomly assigned patients ≥75 years of age with non-ST-segment-elevation ACS to early invasive versus initially conservative strategy. The trial did not report geriatric syndromes including frailty and multimorbidity.…”
Section: Non-st-segment-elevation Myocardial Infarctionmentioning
confidence: 99%
“…To date, of the 5 randomized clinical trials specifically investigating an invasive strategy in older patients with NSTEMI, 4 have found no benefit of invasive treatment on the primary end point compared with conservative management, [130][131][132][133] whereas the other showed that an invasive strategy reduced recurrent MI and urgent repeat revascularization (Table 3). 134,135 The Italian Elderly ACS trial randomly assigned patients ≥75 years of age with non-ST-segment-elevation ACS to early invasive versus initially conservative strategy. The trial did not report geriatric syndromes including frailty and multimorbidity.…”
Section: Non-st-segment-elevation Myocardial Infarctionmentioning
confidence: 99%
“…Open access multimorbidity that present with NSTE-ACS and receive an invasive management strategy. [10][11][12][13] ESC guidelines highlight this important gap in evidence. 6 As the population ages, the proportion of these older patients with multiple chronic conditions and ACS will continue to increase, and data are needed to inform decision-making and discussions with patients and their families.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Multimorbidity has been shown to be associated with adverse outcomes in patients with NSTE-ACS up to 3 years 8 9. However, we lack data to inform the optimal management strategy and longer term prognosis of older adults with multimorbidity that present with NSTE-ACS and receive an invasive management strategy 10–13. ESC guidelines highlight this important gap in evidence 6.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 27 While there is a clear need for individualized, patient-centred care for older patients with NSTEACS, there is a gap in the existing evidence to guide the optimal management in the context of frailty, including the benefit of a routinely applied invasive strategy. 28 , 29 The results of the ongoing British Heart Foundation Older Patients With Non-ST SEgmeNt elevatIOn myocaRdial Infarction Randomized Interventional TreAtment trail (SENIOR-RITA, n = 1600) will be valuable in evaluating the role of invasive management in older adults with NSTEACS in the context of concomitant frailty.…”
Section: Discussionmentioning
confidence: 99%